Temporary DAS Deployment associated with the DEEPEN project in the Hengill region, Iceland (DEEPEN) - Wollin, Christopher; Isken, Marius P.; Jousset, Philippe; Lotte,Krawczyk; Dahm,Torsten (GFZ Data Services, 2023)
Abstract From June to August 2021 the DEEPEN project deployed a dense seismic nodal network across the Hengill geothermal area in southwest Iceland to image and characterize faults and high-temperature zones at high resolution. The nodal network comprised 498 geophone nodes spread across the northern Nesjavellir and southern Hverahlíð geothermal fields and was complemented by an existing permanent and temporary backbone seismic network of a total of 44 short-period and broadband stations. In addition, two fiber optic telecommunication cables near the Nesjavellir geothermal power plant were interrogated with commercial DAS-interrogators. During the time of deployment, a vibroseis survey took place around the Nesjavellir power plant. The here published dataset contains a subset of the downsampled DAS-recordings from the eastern fiber optic array. To save storage space, only every fourth trace was made available. The original data were downsampled from 1000Hz to 250 Hz using the das-convert tool (https://doi.org/10.5880/GFZ.2.1.2021.005). Further traces or the original data can be obtained upon request. Waveform data are available from the GEOFON data centre, under network code ZH.